2011
DOI: 10.1105/tpc.111.084988
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Stresses: Roles of Calcium- and Calcium/Calmodulin-Regulated Gene Expression  

Abstract: Abiotic and biotic stresses are major limiting factors of crop yields and cause billions of dollars of losses annually around the world. It is hoped that understanding at the molecular level how plants respond to adverse conditions and adapt to a changing environment will help in developing plants that can better cope with stresses. Acquisition of stress tolerance requires orchestration of a multitude of biochemical and physiological changes, and most of these depend on changes in gene expression. Research dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
476
1
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 648 publications
(510 citation statements)
references
References 259 publications
(400 reference statements)
5
476
1
10
Order By: Relevance
“…Calcium signaling is known to play an important role in the activation of plant defense responses to abiotic and biotic stresses, e.g., stress-induced phytoalexin biosynthesis (Lecourieux et al 2006;Reddy et al 2011). A number of reports provided evidence that calcium signaling is implicated in the regulation of stilbene biosynthesis.…”
Section: Signaling Pathways Regulating Stilbene Biosynthesis Regulatimentioning
confidence: 99%
“…Calcium signaling is known to play an important role in the activation of plant defense responses to abiotic and biotic stresses, e.g., stress-induced phytoalexin biosynthesis (Lecourieux et al 2006;Reddy et al 2011). A number of reports provided evidence that calcium signaling is implicated in the regulation of stilbene biosynthesis.…”
Section: Signaling Pathways Regulating Stilbene Biosynthesis Regulatimentioning
confidence: 99%
“…It is well known that the typical calmodulin act as Ca 2+ relay by interacting and modulating the activity of target proteins. 1 Experimental evidences demonstrate the ability of CML9 to bind Ca 2+ ions 11 and CML9 was shown to fulfil under certain conditions the role of CaM in yeast. 12 More recently, Perochon et al 13,14 and Popescu et al 15 identified CML9-interacting proteins suggesting that CML9 participates in Ca 2+ -regulated processes in plant.…”
Section: What Could Be the Relationship Between Cml9 And The Flagellimentioning
confidence: 99%
“…1 These Ca 2+ signals are perceived by different Ca 2+ sensors, and calmodulin (CaM) is one of the best characterized Ca 2+ sensors in eukaryotes. Calmodulinlike (CML) proteins extend the Ca 2+ -toolkit in plants; CMLs share sequence similarity with the ubiquitous and highly conserved CaM, however, except for some of them, their roles at physiological and molecular levels remain largely unknown.…”
mentioning
confidence: 99%
“…CaM interacts with a variety of DNA-binding proteins/transcription factors. Over 90 CaM-binding proteins (CBPs) are DNA-binding proteins that fit into several families of known transcription factors, including CAMTAs (also known as AtSRs), WRKY IID, bZIP, MYB, Trihelix, NAC, CBP60, MADS, and GRAS (Reddy et al, 2011a), and the CaMBDs in some of the newly identified CaM-binding transcription factors remain to be determined (Popescu et al, 2007). In this section, we will focus only on recent developments in the direct regulation of Ca 2+ /CaM on transcriptional machinery through the actions of CAMTAs/SRs.…”
Section: Proposed Activation Mechanism Of Ccamkmentioning
confidence: 99%